The Antecedents of Halal Consumption Pattern: The Mediating Role of Muslim Lifestyle, Risk Perception and Trust - Sulaiman, Yaty; Kamariah Nik Mat, Nik; Hasmini Abd Ghani, Noor (International Journal of Engineering and Technology, 2018)
Halal food industry globally experiencing rapid growth which is estimated at USD 2.3 trillion (RM8.3 trillion). Although the halal food market is a fast growing situation, Muslims were sometimes doubtful to consume halal food due to alleged contamination with non-halal ingredients. The question arises of how the specified factors explain halal food consumption. Thus, this paper aims to examine the factors that may influence halal food consumption mediated by risk perception, trust and Muslim lifestyle. Quantitative study has been conducted which consists seven variables measured by a total of 57 Items using seven-point Likert-scale. For this study, data were collected using 240 questionnaires from household consumers. Partial least squares (Smart PLS) were used to analyze the collected data. The ultimate finding implies that all independent variables of halal nutritional knowledge, halal consciousness, green halal consumption and mediator of Muslims lifestyle, risk perception and trust have a significant impact on the halal consumption pattern. Moreover, Muslim lifestyle and risk perception have mediate influence between green halal consumption and halal consumption pattern. As a result, the consumers who choose to consume halal product are practicing green in their consumption. Food and product selection are important for them in order to avoid non-halal food/products which believed this matter aligned to be a good Muslim. Living based on Muslim Lifestyle help to monitor their halal consumption pattern. The finding suggests that producers, including green products producers need to abide to good manufacturing practice to ensure their halal business success.